Comuna de Paris, Estado e Direito / Paris Commune, State and Law. - Carrillo Salgado, Augusto Fernando; García López, Daniel J.; Muñoz Mendiola, Julio César (Revista Direito e Práxis, 2021)
DOI:10.1590/2179-8966/2021/59619. RESENHA Comuna de Paris, Estado e Direito Carla Benítez Martins, Flávio Roberto Batista & Gustavo Seferian (coords.), Comuna de Paris, Estado e Direito. Brasil: Editora RTM, 2021, 635 pp. Daniel J. García López¹ ¹Universidad de Granada, Granada, Espanha. E-mail: danieljgl@ugr.es. ORCID: https://orcid.org/0000-0003-0601-1395. Augusto Fernando Carrillo Salgado² ²Universidad Nacional Autónoma de México (UNAM), Cidade do México, México. E-mail: fernando90@comunidad.unam.mx. ORCID: https://orcid.org/0000-0001-6107-4917. Julio César Muñoz Mendiola³ ³Universidad Nacional Autónoma de México (UNAM), Cidade do México, México. E-mail: julioderecho@comunidad.unam.mx. ORCID: https://orcid.org/0000-0002-8769-7984.